The Influence of Internal and External Factors on Non Performing Financing In Indonesian Shariah Rural Bank And Bank Size As Moderators - Izmiwati, Siti Zahra; Ruhadi (Journal of Applied Islamic Economics and Finance, 2024)
This study investigates the influence of internal and external factors on the probability of experiencing financial difficulties in SRBs, with a particular emphasis on the NPF ratio. Utilized Eviews 12 to conduct panel data regression analysis to examine the impact of the independent variable on the dependent variable, while accounting for the moderating variable. The results suggest that the unemployment rate, GRDP, and CAR factor have a negative impact on the NPF %, with bank size serving as a moderator. The variables FDR, GRDP, unemployment rate, and CAR exhibit a substantial positive influence when moderated by Bank Size. Nevertheless, the FDR variable does not affect NPF when it is regulated by Bank Size.